Interleukin‐1β triggers the differentiation of macrophages with enhanced capacity to present mycobacterial antigen to T cells. Issue 2 (February 2014) - Schenk, Mirjam; Fabri, Mario; Krutzik, Stephan R.; Lee, Delphine J.; Vu, David M.; Sieling, Peter A.; Montoya, Dennis; Liu, Philip T.; Modlin, Robert L.
Summary The rapid differentiation of monocytes into macrophages (MΦ) and dendritic cells is a pivotal aspect of the innate immune response. Differentiation is triggered following recognition of microbial ligands that activate pattern recognition receptors or directly by pro‐inflammatory cytokines. We demonstrate that interleukin‐1β (IL‐1β) induces the rapid differentiation of monocytes into CD209+ MΦ, similar to activation via Toll‐like receptor 2/1, but with distinct phenotypic and functional characteristics. The IL‐1β induced MΦ express higher levels of key markers of phagocytosis, including the Fc‐receptors CD16 and CD64, as well as CD36, CD163 and CD206. In addition, IL‐1β‐induced MΦ exert potent phagocytic activity towards inert particles, oxidized low‐density lipoprotein and mycobacteria. Furthermore, IL‐1β‐induced MΦ express higher levels of HLA‐DR and effectively present mycobacterial antigens to T cells. Therefore, the ability of IL‐1β to induce monocyte differentiation into MΦ with both phagocytosis and antigen‐presenting function is a distinct part of the innate immune response in host defence against microbial infection.